Curcuma arida and C. sahuynhensis, two new species from subgenus Ecomata (Zingiberaceae) from Vietnam - Leong-Škorničková, Jana; Lý, Ngọc-Sâm; Nguyễn, Quốc Bình (Phytotaxa, 2015)
Two new Curcuma species are described and illustrated from Vietnam. They are compared to their closest allies from subgenus Ecomata. Curcuma arida from Núi Chúa National Park, Ninh Thuận Province, is compared to Curcuma pambrosima and C. vitellina, while Curcuma sahuynhensis from Quảng Ngãi Province is compared to Curcuma xanthella.